AB1156 Involvement of Patient Research Partners in Clinical Research: Recommendations Developed by Omeract. (9th June 2015) - Cheung, P.; De Wit, M.; Bingham, C.O.; Kirwan, J.; Leong, A.; March, L.; Montie, P.; Scholte-Voshaar, M.; Gossec, L.
Abstract : Background: Patient participation in research is increasing; however, practical guidelines to enhance this participation are lacking. Specifically within the Outcome Measures in Rheumatology (OMERACT) organization, although patients have participated in OMERACT meetings since 2002, consensus about the procedures for involving patients in working groups has not been formalized. Recommendations would therefore be useful, both within OMERACT and for clinical research projects at both national and international levels. Objectives: To develop a set of recommendations regarding patient research partner (PRP) involvement in research projects. Methods: (i) systematic literature review on recommendations/guidelines of PRP involvement in research; (ii) structured consensus process based on a draft set of recommendations developed by a working group of 4 clinicians and 4 patient research partners, with then involvement of multiple stakeholders during the OMERACT 2014 meeting in May 2014 (iii) endorsement of recommendations by OMERACT. Results: (i) In the 18 articles included in the literature review [1], there was general agreement on the broad concepts for recommendations covering PRP involvement in research although they were heterogeneous in detail. Most considered PRP involvement in all phases of research with early engagement, training and support important, but details on the content were scarce. (ii) From this review, a structured consensus process led by the working group resulted in three over-arching principles and 8 recommendations which were developed, discussed, and refined at OMERACT 2014. The guiding principles were endorsed during the OMERACT plenary session by 99% of participants and subsequently by the OMERACT steering committee. Conclusions: Recommendations to formalize and enhance PRP involvement in OMERACT research projects have been developed and endorsed. These reinforce the importance of patient participation throughout the research process as integral members and will enable a research agenda to evaluate their implementation and impact on outcome development. These recommendations can potentially be applied for PRP in clinical research settings other than OMERACT. References: Cheung P, de Wit M, Gossec L. Ann Rheum Dis 2014;73(Suppl2):619-620. Disclosure of Interest: None declared